Hegemoni Budaya Jepang Dalam Gaya Hidup Cosplayer (Studi Sosiologi Pada Komunitas Cosplay Makassar Suki di Makassar) - Anggraeni, Neti; Suhaeb, Firdaus W; Nur, Hasruddin (Universitas Negeri Makassar, 2021)
The study aims at (i) describing the process of Japanese cultural hegemony in Cosplayer lifestyle in the community of COMASU (Cosplay Makassar Suki) in Makassar, (ii) analyzing the factors that cause the hegemony of Â Japanese culture in Cosplayer lifestyle in the community of COMASU. This study is descriptive qualitative with sociology approach, aims at describing the phenomena of Japanese cultural hegemony in Cosplayer lifestyle in the community of COMASU. Data collection techniques were observation, interview, and documentation. Data validity technique used source triangulation to examine the credibility of data conducted, done by checking the data obtained through several sources. The results of study discovered that (i) the process of Japanese cultural hegemony in Cosplayer lifestyle in the community of COMASU in Makassar started from the cultural learning process through internalization process, socialization process, and enculturation process. It went through culture development process, namely culture evolution process and diffusion process. (ii) From the process, it obtained the cause of Japanese cultural hegemony in Cosplayer lifestyle in the community of COMASU, namely attitude and personality, experience and observation, motive or need, family and influence of media.